How does ridesplitting reduce emissions from ridesourcing? A spatiotemporal analysis in Chengdu, China. (June 2021) - Li, Wenxiang; Pu, Ziyuan; Li, Yuanyuan; Tu, Meiting
Highlights: Ridesplitting reduces the emission factors per ride-km of ridesourcing by 28.7–32.5% on average. Ridesplitting reduces more emissions around the expressways and during peak hours. A spatial error model is used to identify the influencing factors of the emission reductions. The emission reductions are correlated to travel-related and built environment variables. The trajectory overlapping ratio is most important to expand the environmental benefits. Abstract: Ridespitting, which enables riders with similar routes to share a ridesourcing trip, is a promising transportation technology to reduce traffic congestions and air pollutions. This study aims to explore how ridesplitting reduces emissions from ridesourcing based on GPS trajectory data from Didi Chuxing in Chengdu, China. First, this study quantifies the emission factors of both regular ridesourcing and ridesplitting trips to evaluate the emission reductions per ride-km from ridesplitting. The results show that the average emission reduction rates of CO2, CO, NOx, and HC are 28.7%, 32.5%, 27.7%, and 31.2%, respectively. Then, a spatiotemporal analysis of the emission reductions indicates that ridesplitting generally reduces more emissions around the expressways and during peak hours. Finally, a spatial error model is adopted to analyze the effects of travel-related and built environment variables on emission reductions from ridesplitting. The trajectory overlapping rate of shared rides turns out to be the most important determinant for expanding the environmental benefits of ridesplitting.